Social Media Regulation in the Post-Truth Era: Analysis of Dezinformation Handling Policies in Indonesia - Bustami, Bustami; Sazali, Hasan (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
The post-truth era is characterized by the increasing spread of information that prioritizes emotions and opinions over objective facts. Social media serves as the main channel for the distribution of this information, often without adequate supervision, increasing the risk of spreading misinformation. In Indonesia, the complexity of this challenge is increasing along with the high penetration of social media and the low level of digital literacy among the public. This article aims to analyze government policies in dealing with disinformation in the post-truth era through social media regulation. This study uses a qualitative approach with a policy analysis method, which includes a review of existing regulations such as the ITE Law, the Regulation of the Minister of Communication and Information, and other initiatives related to digital literacy. The results of the study show that existing regulations are not yet fully effective in dealing with disinformation, due to technical challenges, such as platform algorithms that tend to favor sensational content, as well as normative challenges related to freedom of expression. This study also reveals that collaboration between the government, social media platforms, and civil society is essential to creating a healthy digital ecosystem. The proposed recommendations include increasing digital literacy, strengthening regulations based on human rights, and developing technology to detect disinformation. This article contributes to the development of more effective and inclusive policies in facing the challenges of the post-truth era in Indonesia.